Impact of empiric antibiotics for methicillin-resistant Staphylococcus aureus (MRSA) infection and associated Clostridioides difficile infection (CDI) risk: Secondary analysis of the CLEAR trial. (16th December 2021) - Weiland, Anastasiia S.; Lu, Julia Y.; Chen, Caleb S.; Tjoa, Thomas; Singh, Raveena; McKinnell, James A.; Miller, Loren G.; Huang, Susan S.
ABSTRACT: We performed secondary analyses of a postdischarge decolonization trial of MRSA carriers that reduced MRSA infection and hospitalization by 30%. Hospitalized MRSA infection was associated with 7.9 days of non-MRSA antibiotics and CDI in 3.9%. Preventing MRSA infection and associated hospitalization may reduce antibiotic use and CDI incidence.